Butyrate Shapes Immune Cell Fate and Function in Allergic Asthma - Yip, William; Hughes, Michael R.; Li, Yicong; Cait, Alissa; Hirst, Martin; Mohn, William W.; McNagny, Kelly M. (Frontiers in Immunology, 2021)
The microbiome plays a fundamental role in how the immune system develops, is shaped and regulated. The ‘gut-lung axis’ is a relatively new term that highlights a crucial biological crosstalk between the intestinal microbiota and the lungs. A growing body of literature suggests that dysbiosis, perturbation of the gut microbiota, is a driving force behind the development and severity of allergic asthma. Animal models have given researchers new insights into how gut microbe-derived components and metabolites, such as short-chain fatty acids (SCFAs), influence the development of asthma. While the full understanding of how SCFAs influence allergic airway disease remains obscure, a recurring theme of epigenetic alterations in gene expression in several immune cell compartments is emerging. This review will address our current understanding of how SCFAs, and specifically butyrate, orchestrates cell behaviour and epigenetic changes and will provide a detailed overview of the effects of these modifications on immune cells in the context of allergic airway disease.